Critical Discourse Analysis of Vegan Diet on Detik.com Online Media - As Shofi, Salsabila (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the discourse on vegan diets based on articles from Detik.com, utilizing Fairclough’s Three-Dimensional Framework. The analysis focuses on ten data points that illustrate individual experiences and the role of media in shaping narratives around dietary practices. The texts emphasize personal experiences, such as Bella, Victoria Ferraz, and Robert Downey Junior transitioning from vegan to carnivore diets due to health concerns, including nutritional deficiencies, skin problems, and low energy levels. Conversely, Cantika Abigail highlights the positive impact of a vegan diet on her autoimmune condition. Media leverages these experiences to frame veganism as a modern and healthy lifestyle while accommodating resistance through narratives of transitioning to animal-based diets. The discursive practices reveal that media serves not only as an intermediary of information but also as a trendsetter, shaping public perceptions through selective storytelling. The social practices identified in this analysis highlight the complexity of dietary choices, influenced by individual health needs, societal demands for sustainability, and ethical consumption issues. This pattern underscores how diet is not merely a personal decision but part of a broader social discourse, where media acts as a central agent in shaping public views on health and lifestyle.